Exploring Ecological Rituals of Indigenous People in Indonesia Amid the COVID-19 Pandemic - Nikodemus Niko (Journal of Religion and Social Transformation, 2024)
The COVID-19 pandemic har far-reaching impacts on economic, political, and social aspects of indigenous communities worldwide, including those in Indonesia. This study delves into the often overlooked effects of the pandemic, exposing cases of poverty, hunger, and limited access to healthcare among indigenous peoples. Utilizing a non-systematic literature review method, the research aims to uncover the meanings and significance of ecological rituals for indigenous women in Indonesia. The study critically evaluates relevant literature, identifying key themes and patterns related to these rituals within cultural, social, and environmental contexts. Results indicate that indigenous women exhibit strong resilience during the pandemic, rooted in communal living and close community bonds. Social restrictions have minimal impact on their traditional activities, and various rituals serve as effective coping mechanisms, fostering psychological well-being. This research contributes to understanding the ecological knowledge, practices, and beliefs of indigenous women, offering insights for sustainable development and conservation efforts.